Pengaruh Pelatihan (Training), Pelayanan Karyawan Dan Loyalitas Kerja Karyawan Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pada Karyawan PT Karya Giri Palma) - Nur Wulan Putri Lestari; Nur Hajati; Muhammad Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research is used to analyze and determine the effect of training, employee service and employee work loyalty to employe work productivity on PT Karya Giri Palma. The method used is explanatory research with a quantitative approach. The sample in this study were employees of PT Karya Giri Palma.The result indicate that the variables of training, employee service and work loyalty simultaneously affected the work productivity of employees. This is indicated by value Fhitung > Ftabel. The training variable is known partially does not have a significant effect on employee work produvtivity. As well as employee service variables that partially do not significantly influence employee productivity. Whereas the employee work loyalty variable partially has a significant effect on employee productivity.Keyword : training, employee service, work loyalty, work produktivity